PENGEMBANGAN PERANGKAT LUNAK UNTUK PENERAPAN TEKNIK PINCH DENGAN MELIBATKAN KENDALA RUGI TEKANAN - Adriansyah, Willy; Suwono, Aryadi (Mesin, 1996)
The existing software of pinch technique provide only the tool for the heat exchanger network design. To improve the reliability of the software, in particularly for retroï¬tting the existing system, several additional aspects need to be included. In this paper, an algorithm to determine the optimum condition of heat exchangers for a specified allowable head loss is proposed. With this new method, the retroï¬t design of an existing system can be done even by taking into consideration of using the existing ï¬uid circulation systems (i.e. pumps and compressors). The proposed method of heat exchanger can also be used under the pressure drop constraints on both tube and shell sides.